2020
DOI: 10.1002/mrm.28516
|View full text |Cite
|
Sign up to set email alerts
|

A fast multislice sequence for 3D MRI‐CEST pH imaging

Abstract: Purpose: Chemical exchange saturation transfer MRI can provide accurate pH images, but the slow scan time (due to long saturation periods and multiple offsets sampling) reduce both the volume coverage and spatial resolution capability, hence the possibility to interrogate the heterogeneity in tumors and organs. To overcome these limitations, we propose a fast multislice CEST-MRI sequence with high pH accuracy and spatial resolution. Methods: The sequence first uses a long saturation pulse to induce the steady-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 73 publications
(179 reference statements)
0
33
0
Order By: Relevance
“…For example, the combination of a long primary and several short secondary saturation pulses where 1 secondary saturation is added to each subsequent imaging slice to compensate for T 1 recovery. 10,60 With ASEF, both the primary and the secondary saturation can be selected as high or low DC pulse trains with different pulse durations, respectively. Similarly, ASEF can also be incorporated into 3D imaging sequences.…”
Section: F I G U R Ementioning
confidence: 99%
“…For example, the combination of a long primary and several short secondary saturation pulses where 1 secondary saturation is added to each subsequent imaging slice to compensate for T 1 recovery. 10,60 With ASEF, both the primary and the secondary saturation can be selected as high or low DC pulse trains with different pulse durations, respectively. Similarly, ASEF can also be incorporated into 3D imaging sequences.…”
Section: F I G U R Ementioning
confidence: 99%
“…In addition, we optimized the LATEST imaging protocol for 3 T MRI scanners, the field strength commonly used in clinical practice. However, compared to high-field MRI systems with 7 T and more, the optimized imaging protocol must be considered less sensitive; in particular, higher field strengths allow for volumetric multi-slice approaches due to the higher SNR, whereas our measurements record only one slice [ 54 ]. Furthermore, the in vitro experiments showed that pH changes in a physiological range of 7.0–7.3 can be neglected compared to the change in lactate levels.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our proposed approach combines both an efficient noise‐reduction algorithm and the redundancy of spatial information inside the image to improve the CEST contrast quantification. Finally, we think that the proposed approach could potentially also be widely exploited for the denoising of other CEST‐MRI applications, both for pH imaging as well as for GlucoCEST or APT imaging, 71‐73 after optimizing and evaluating the proposed denoising method for each CEST modality. Moreover, we want to emphasize that, before any application, either in a human whole‐body scanner or in conjunction with parallel imaging, further investigations concerning the influence of B 0 and B 1 inhomogeneities and non‐Rician noise distribution are required to verify the applicability of the approach.…”
Section: Discussionmentioning
confidence: 99%